Richard III : Propeller Shakespeare. - Shakespeare, William (Oberon Books, 2015)
Richard III brings the Wars of the Roses cycle of history plays to a close in bloody fashion. Arguably Shakespeare's most villainous king, we watch in horror and delight as Richard murders his way to the throne, unable to resist his cruel wit and dark humour. This is a hugely entertaining and diabolical adventure that tells the story of one man's journey to heaven, then back to hell.